Larval growth and condition of eastern Baltic cod (Gadus morhua L.) in the laboratory : Effects of key environmental factors - Meyer, Stefan (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2012)
The early life stages of marine fish are susceptible to the effects of abiotic environmental and intrinsic and extrinsic biotic factors. Water temperature and feeding levels are among the most important of these. The interaction of all these factors determines the individual fate of an egg or a larva as much as it does affect a cohort or a population. Describing the effects of these environmental factors on larval growth, condition and survival under controlled laboratory conditions is essential to understand the mechanisms of recruitment in the field. The Eastern Baltic cod population has attracted a lot of scientific interest, but fundamental knowledge on the vital rates of the larval stages under controlled conditions in the laboratory has been lacking. In the framework of this thesis, I reared Eastern Baltic cod larvae from hatching until the late pre-metamorphosis stage and performed experiments on the effects of water temperature and feeding levels on growth and condition, the effect of temperature, body size and species on starvation-induced changes in condition, the effect of fluorescence marking on vital rates of eggs and larvae and the effect of different “green water” types on early larval feeding activity and survival. As a result of these experiments, I described the somatic and otolith growth, morphological and biochemical condition of Eastern Baltic cod larvae and parameterized growth models for these parameters. This knowledge can be used to compare the vital rates of larvae from different cod populations and to estimate recent growth rates from biochemical condition. I also compared rates of change in biochemical condition, biochemical thresholds and time to death as proxies for physiological processes under food-deprivation and found species-specific adaptations to withstand the effects of starvation in eight different species. Further, I found sublethal chronic effects on vital rates of Eastern Baltic cod eggs and larvae that were marked with Alizarin Complexone and I formulated ...